Efektivitas Bahan Ajar Buku Panduan PembelajaranKebencanaan Kabupaten Klaten Pada Bencana BanjirDengan Menggunakan Strategi Index Card MatchTerhadap Hasil Belajar Di SMK Kristen 5 Klaten - Aryani, Klife; Taurat Aly, Dra.Siti Taurat Aly, M.Pd (2016)
Christian SMK 5 Klaten located at Jl. Metuk village opaque Tegalyoso District of Klaten district. The use of learning strategies are indispensable in the learning process because it can give susana class becomes more active, and learning outcomes will be achieved in accordance with what is desired. The purpose of this study was to examine the effectiveness of the book Subjects Disaster Guide Klaten Regency assisted learning strategies Index Card match the material to the students flood disaster preparedness school extracurricular classes in vocational Christian X 5 Klaten. The research method was experimental with a population of extracurricular school students of class X SMK disaster preparedness Christian 5 Klaten, divided into class A and class B. pembelajaranya experiment in using the strategy of Index Card Match while pembelajaranya control class by using the conventional method. Experimental class with 30 students for the control class there are 33 students. The study concluded that (1) the use of strategies Index Card Match on book Disaster Learning Guide Klaten district in the floods in the Christian vocational class 5 Klaten experiment showed the average value of student learning outcomes at 62.20 which is the average value of pre test then increased to 76.98 average yield testnya post. While the average of the control class shows the results of the pre test 59.52 while the average for post testnya 71.25. (2) by Mann Whitney test showed no difference between the experimental class and control class, but when viewed from the average value of 71.25 students learning class control while 76.98 for an experimental class, the increase in the average value of the results student learning experiment was higher than the control class.